Integrated Virtual Laboratory with 5E Learning Cycle: A Solution to Enhance Students' Science Process Skills in Reaction Rate Material - Christinemon Kiding Allo; Suwardi (Universitas Pendidikan Ganesha, 2026)
The low level of students’ science process skills in reaction rate material is attributed to the limited implementation of practical activities in real laboratory settings. In addition, conventional instructional approaches have not adequately facilitated students’ active engagement in independently constructing scientific concepts. Therefore, this study aims to analyze and evaluate the effectiveness of an integrated virtual laboratory based on the Learning Cycle 5E model in enhancing students’ science process skills. This research employed a quasi-experimental design with a control group. The participants consisted of 68 eleventh-grade students, divided into an experimental class (34 students) and a control class (34 students). Data were collected using essay-based tests aligned with science process skills indicators, administered through pre-test and post-test instruments. Data analysis was conducted using paired-sample t-tests and N-gain analysis. The results indicated that the experimental class demonstrated a higher improvement, with an average post-test score of 61.35 compared to 29.97 in the control class, and achieved a medium N-gain category (0.53). In conclusion, the use of an integrated virtual laboratory based on the Learning Cycle 5E model is effective in improving students’ science process skills. The implications of this study emphasize the importance of integrating technology and innovative learning models to create more meaningful and student-centered chemistry learning.